Liver proteomics of gilthead sea bream (Sparus aurata) exposed to cold stress. (May 2019) - Ghisaura, S.; Pagnozzi, D.; Melis, R.; Biosa, G.; Slawski, H.; Uzzau, S.; Anedda, R.; Addis, M.F.
Abstract: The gilthead sea bream ( Sparus aurata, L. ) is very sensitive to low temperatures, which induce fasting and reduced growth performances. There is a strong interest in understanding the impact of cold on fish metabolism to foster the development and optimization of specific aquaculture practices for the winter period. In this study, an 8 week feeding trial was carried out on gilthead sea bream juveniles reared in a Recirculated Aquaculture System (RAS) by applying a temperature ramp in two phases of four weeks each: a cooling phase from 18 °C to 11 °C and a cold maintenance phase at 11 °C. Liver protein profiles were evaluated with a shotgun proteomics workflow based on filter-aided sample preparation (FASP) and liquid chromatography-mass spectrometry (LC-ESI-Q-TOF MS/MS) followed by label-free differential analysis. Along the whole trial, sea breams underwent several changes in liver protein abundance. These occurred mostly during the cooling phase when catabolic processes were mainly observed, including protein and lipid degradation, together with a reduction in protein synthesis and amino acid metabolism. A decrease in protein mediators of oxidative stress protection was also seen. Liver protein profiles changed less during cold maintenance, but pathways such as the methionine cycle and sugar metabolism were significantly affected. These results provide novel insights on the dynamics and extent of the metabolic shift occurring in sea bream liver with decreasing water temperature, supporting future studies on temperature-adapted feed formulations. The mass spectrometry proteomics data have been deposited to the ProteomeXchange Consortium via the PRIDE partner repository with the dataset identifier PXD011059. Graphical abstract: Image 1 Highlights: Exposure to cold temperature modifies the sea bream liver protein abundance profile. Proteolysis and aminoacid catabolism are most affected during temperature decrease. Methionine cycle and sugar metabolism are most affected upon prolonged cold stress. Shotgun proteomics complements the data on hepatic metabolism changes following cold stress.